Current Applications of Facial Volumization with Fillers. Issue 5 (May 2016) - Wilson, Anthony J.; Taglienti, Anthony J.; Chang, Catherine S.; Low, David W.; Percec, Ivona
Abstract : Learning Objectives: After reading this article and watching the accompanying videos, the participant should be able to: 1. Assess patients seeking facial volumization and correlate volume deficiencies anatomically. 2. Identify appropriate fillers based on rheologic properties and anatomical needs. 3. Recognize poor candidates for facial volumization. 4. Recognize and treat filler-related side effects and complications. Summary: Facial volumization is widely applied for minimally invasive facial rejuvenation both as a solitary means and in conjunction with surgical correction. Appropriate facial volumization is dependent on patient characteristics, consistent longitudinal anatomical changes, and qualities of fillers available. In this article, anatomical changes seen with aging are illustrated, appropriate techniques for facial volumization are described in the setting of correct filler selection, and potential complications are addressed. Abstract : Related Video Content is Available Online.